Photography, the Cinema, Sound Recording: beginnings and introduction in Brazil - Lima, Guilherme Cunha; Lessa, Gerson (InfoDesign, 2008)
This paper shows how the unique characteristics of plastics made possible the development of mass communication technology (photography, the cinema and sound recording). It shows how, in a period of low industrialization in Brazil, the use of plastics is established in the production of phonograph records when the Odeon factory starts producing locally what had been made abroad.